PENGARUH DIMENSI KUALITAS LAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT PENGGUNA TRANS MAMMINASATA - Yulianto, Harry; Yahya, Syarief Dienan (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Public transportation such Bus Rapid Transit (BRT) as an alternative solution used of cities in Indonesia to overcome traffic congestion problem. This research will test the effect of public service quality dimension to the citizen satisfaction of Trans Mamminasata users. The sample of this research are people who have used Trans Mamminasata transportation modes at least one time. Sampling technique of this research use non probability sampling, with purposive sampling method. The variables used in this research consist of independent variables (public services quality) and dependent variable (citizen satisfaction). Public service quality variables was measured using five dimensions, such us reliability, responsiveness, tangible, assurance, and empathy. Techniques of data collection in this research for hypothesis testing was using questionnaires. In this study, the instrument of validity test was was using Confirmatory Factor Analysis (CFA), and reliability test was using cronbach's alpha correlation. The test of hypotheses in this study were using different data analysis techniques, namely: simple linear regression (H 1 , H 2 , H 3 , H 4 , H 5 ) and multiple linear regression (H 6 ).The results of this research were showed that H 1 was rejected. Meanwhile, H 2 , H 3 , H 4 , H 5 and H 6 were accepted.